PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING UMKM KULINER DI KECAMATAN SUKMAJAYA - Anisa Tri Pujianti (2022)
This research aims to determine and analyze the effect of market orientation and product innovation on the competitive advantage of culinary MSME in Sukmajaya District. The population in this research were culinary MSME in Sukmajaya District and 111 respondents were taken as samples. Probability sampling is the method used in this research. The test equipment in this research used Partial Least Square, with a significance of 5%. The results of this research show that: (1) there is a significant influence on market orientation on the competitive advantage of MSME (2) there is a significant influence on product innovation on the competitive advantage of MSME. Researchers suggest MSME to pay attention to other factors that affect competitive advantage.